Characterization of the first complete chloroplast genome of Amaranthus hybridus (Caryophyllales: Amaranthaceae) with phylogenetic implications. Issue 11 (2nd November 2021) - Bai, Xue; Ye, Xueling; Luo, Yiming; Liu, Changyin; Wu, Qi
Abstract: In the present study, the complete chloroplast genome of Amaranthus hybridus was sequenced and assembled. The complete chloroplast genome of Amaranthus hybridus is 150, 709 in size, with the GC content of 36.56%. The chloroplast genome of Amaranthus hybridus contained 86 protein-coding genes (PCGs), eight ribosomal RNA (rRNA) genes, and 37 transfer RNA (tRNA) genes. Phylogenetic analysis based on combined chloroplast gene dataset indicated that the Amaranthus hybridus exhibited a close relationship with A. hypochondriacus and A. caudatus .